Catheter ablation in combined procedures is associated with residual leaks - Zhu, Xuefeng; Li, Wenjing; Chu, Hongxia; Zhong, Lin; Wang, Chunxiao; Li, Jianping; Liang, Pingping; Wang, Lihong; Shi, Lei (Frontiers in Cardiovascular Medicine, 2023)
Objectives: Atrial fibrillation (AF) patients undergoing left atrial appendage closure (LAAC ) with and without catheter ablation (CA) were compared. Background: The CA of AF may cause ridge edema, which may affect the safety of LAAC. Methods: AF patients (N = 98) who went through LAAC (combined CA+LAAC procedures group; N=51), alone (LAAC group; N = 47) received transesophageal echocardiography (TEE) pre-procedural, intra-procedural and six-weeks post-procedure. The depth and ostial diameter of LAA, device compression, residual leak, and ridge thickness were evaluated in the patients who having undergone combined and alone procedures, as well as images of LAA and primary clinical characteristics. Results: 27 patients were identified with a residual leak at six-weeks after implantation by TEE (19 in the combined procedures group and 8 in the alone group; p = 0.04). The rate of new residual leak was observed in the combined procedures group was significantly higher than in the alone group (25.5% vs 8.5%; p = 0.03). Meanwhile, compared with at the time of implanted, a smaller amount of device compression ratio was significant after six-weeks (22.44 ± 3.90 vs19.59 ± 5.39; p = 0.03). No significance between both groups in all-cause, or cardiovascular deaths, and TIA/stroke/system embolism. Conclusions: Combined procedures of CA and LAAC for AF are feasible and safe, however, during follow-up period, we found that resolution of ridge edema caused by CA might cause increased residual leak and smaller device compression ratio.